Anatomy of the caecum, appendix and colon. Issue 3 (March 2017) - Mahadevan, Vishy
Abstract: For descriptive purposes the large intestine is divided, successively, into the caecum and appendix, colon, rectum and anal canal. The colon is further subdivided into ascending, transverse, descending and sigmoid segments. The sigmoid colon crosses the pelvic brim to enter the pelvic cavity where it becomes continuous with the rectum. Embryologically, the proximal half of the large intestine is derived from the midgut, while the distal half develops from the hindgut. This dual derivation is reflected in the proximal half of the large intestine being supplied by the superior mesenteric artery and the distal half by the inferior mesenteric artery; the arteries of the embryological midgut and hindgut respectively. The principal physiological role of the large intestine is the absorption of water, sodium and chloride from the fairly large volume of liquid ileal contents delivered to the large intestine daily. The unabsorbed residue is excreted as faeces. Fibreoptic colonoscopy and MRI and CT colonography allow detailed internal inspection of the large intestine with relative ease and speed and without subjecting the patient to too much discomfort. This article emphasizes the clinically and surgically-relevant aspects of the anatomy of the caecum, appendix and colon.